The Effect of Classical Massage with Different Oils on Nonspecific Chronic Low Back Pain and Function - Kristina Venckūnienė; Vaida Pokvytytė; Vida Ostasevičienė; Gerda Kazlauskaitė; Jūratė Požėrienė; Diana Rėklaitienė (Lithuanian Sports University, 2019)
Research background. Chronic nonspecifc low back pain is one of the most widespread health problems in modern society. Massage together with oils is commonly used for low back pain. However, no studies are available on the eﬀect of classical massage with diﬀerent oils on functional state and pain in patients with chronic low back pain. The aim of this research was to determine the eﬀects of classical massage with diﬀerent oils on patients with chronic nonspecifc low back pain. Methods. This study included 14 women. They were randomly assigned into two groups. The experimental group received classical massage using oil of natural components and the control group received massage with Vaseline oil. All participants received seven massage sessions, one session lasted 20 min. Pain intensity (VAS scale), functional disability level (Oswestry Low Back Disability Questionnaire) and measurement of spine ﬂexion range of motion (Modifed Shober test) were evaluated before and after intervention. Results. Both groups showed signifcant improvements in pain intensity (p < 0.05). Massage with oil of natural components was more eﬀective then massage with Vaseline oil in reducing pain (p < 0.05). Functional disability decreased in both groups (p < 0.05), but no signifcant diﬀerence was found between groups. The range of motion changes were not signifcant after intervention in two groups. Conclusions. Classical massage with oil of natural components and classical massage with Vaseline oil were found to be eﬀective in relieving pain and decreasing functional disability in patients with chronic low back pain. Massage with oil of natural components was more eﬀective than massage with Vaseline oil in reducing pain. Keywords: chronic nonspecifc low back pain, classical massage, oil.